Genetic predictors of acute toxicities related to radiation therapy following lumpectomy for breast cancer: a case-series study - Ambrosone, Christine; Tian, Chunqiao; Ahn, Jiyoung; Kropp, Silke; Helmbold, Irmgard; Fournier, Dietrich von; Haase, Wulf; Sautter-Bihl, Marie-Luise; Wenz, Frederik; Chang-Claude, Jenny (Breast cancer research, 2006)
Introduction The cytotoxic effects of radiation therapy are mediated primarily through increased formation of hydroxyl radicals and reactive oxygen species, which can damage cells, proteins and DNA; the glutathione S-transferases (GSTs) function to protect against oxidative stress. We hypothesized that polymorphisms encoding reduced or absent activity in the GSTs might result in greater risk for radiation-associated toxicity. Methods Women receiving therapy in radiation units in Germany following lumpectomy for breast cancer ( 1998 - 2001) provided a blood sample and completed an epidemiological questionnaire (n = 446). Genotypes were determined using Sequonom MALDI-TOF (GSTA1, GSTP1) and Masscode (GSTM1, GSTT1). Biologically effective radiotherapy dose (BED) was calculated, accounting for differences in fractionation and overall treatment time. Side effects considered were grade 2c and above, as classified using the modified Common Toxicity Criteria. Predictors of toxicity were modelled using Cox regression models in relation to BED, with adjustment for treating clinic, photon field, beam energy and boost method, and potential confounding variables. Results Low activity GSTP1 genotypes were associated with a greater than twofold increase in risk for acute skin toxicities ( adjusted hazard ratio 2.28, 95% confidence interval 1.04 - 4.99). No associations were noted for the other GST genotypes. Conclusion These data indicate that GSTP1 plays an important role in protecting normal cells from damage associated with radiation therapy. Studies examining the effects of GSTP1 polymorphisms on toxicity, recurrence and survival will further inform individualized therapeutics based on genotypes.